Hannah Arendt's political thinking on emotions and education: implications for democratic education. Issue 4 (3rd July 2020) - Zembylas, Michalinos
ABSTRACT: This paper asks: when political emotions are invoked in the classroom, can this be done without the process of democratic education degenerating into a form of emotional and/or political indoctrination? The source of inspiration for addressing this question is Hannah Arendt's political thought on emotion and education. The aim of the article is to show that despite the tensions and weaknesses that have been identified over the years about Arendt's views on both emotions and political education, she provides compelling insights against the possibilities of political education degenerating into moral-emotional rhetoric. Arendt highlights the dangers of constructing political emotions in the classroom as the foundation for political action, while acknowledging the constructive role for the emotions in the development of political agency. The paper concludes that Arendt's insights on emotions and political education can help educators avoid potential pitfalls in efforts that (re)consider the place of political emotions in the classroom.